DIRECTIONS AND TRENDS OF REGIONAL INTELLIGENT SPECIALIZATION IN BULGARIA - P. Atanasova (Trakia Journal of Sciences)
The aim of the report is to draw up the directions for development of the regions in the country, as well as leading trends in intelligent specialization. The starting points are analyzes of the Ministry of Economy and European Business Institute, taking into account the changes in the positions of Bulgaria according to the Global innovation index. Trends in the main innovative activities at NUTS 2 regional level were reported by analyzing objective statistical data of the National Statistical Institute. The changes at the national level in the three production technology groups have also been studied (low-tech, medium-tech, high-tech) as a precondition for regional structural change. Specifying the development trends in the main territorial units in the country will result in a focus on the areas concerned and targeting financial resources to places with the highest potential and perspective.